Makna dari Konsep “Litaarafu” dalam Perdagangan Internasional - Huda, Miftahul (Universitas Muhammadiyah Yogyakarta, 2022)
International trade is something that is commonly done by countries in the era of globalization. International Trade applies the concept of Free Trade which is supervised by an international institution called the WTO. In the long run, the application of free trade has not changed many countries that are still declared to be developing into developed countries. So that in this paper, one of the Islamic concepts will be described, namely lita'arafu, where knowing each other is also one of the conditions for conducting international trade. The research method is carried out with a descriptive literature review - an analysis to compare the concept of free trade with the concept of Islam in the meaning of litaarafu. Getting to know each other here is more emphasized on how countries that carry out trade, use the fair trade system, do not take arbitrary actions by respecting the rules that have been formed and mutually agreed upon, helping each other, and not being hostile to each other among the countries that have is trading.